2022
DOI: 10.1155/2022/6972624
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-tTg-IgA among Symptomized Celiac Disease Patients and Their Correlation with Rotavirus Infection

Abstract: Celiac disease (CD) is a chronic inflammatory disorder in the intestinal tract as a response to the use of gluten in genetically predisposed individuals. It is a worldwide problem, with a high prevalence rate in North America. This is a descriptive cross-sectional study involving 1090 samples collected from different hospitals of Rawalpindi and Islamabad, Pakistan, from January 2019 to December 2019. In this study, 1090 blood samples screened for seroprevalence of anti-tTG antibodies in CD symptomatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Previous studies showed a link between rotaviruses and CD [71][72][73]. VP7 is a protein of the outer layer of rotavirus.…”
Section: Rotavirusmentioning
confidence: 99%
“…Previous studies showed a link between rotaviruses and CD [71][72][73]. VP7 is a protein of the outer layer of rotavirus.…”
Section: Rotavirusmentioning
confidence: 99%